Depression and Accelerated Aging: The Eveningness Chronotype and Low Adherence to the Mediterranean Diet Are Associated with Depressive Symptoms in Older Subjects - Sorlí, José V.; de la Cámara, Edurne; Fernández-Carrión, Rebeca; Asensio, Eva M.; Portolés, Olga; Ortega-Azorín, Carolina; Pérez-Fidalgo, Alejandro; Villamil, Laura V.; Fitó, Montserrat; Barragán, Rocío; Coltell, Oscar; Corella, Dolores (Nutrients, 2025)
Background and objectives: Depression often results in premature aging, which increases the risk of other chronic diseases, but very few studies have analyzed the association between epigenetic biomarkers of aging and depressive symptoms. Similarly, limited research has examined the joint effects of adherence to the Mediterranean diet (MedDiet) and chronotype on depressive symptoms, accounting for sex differences. Therefore, these are the objectives of our investigation in a Mediterranean population at high cardiovascular risk. Methods: We analyzed 465 older subjects (aged 55–75) with metabolic syndrome and assessed depressive symptoms by the Beck Depression Inventory (BDI-II). MedDiet adherence was measured with the 17-item MedDiet score, and chronotype with the Morningness–Eveningness Questionnaire (MEQ). Blood DNA methylation was analyzed, and epigenomic biomarkers of age acceleration were determined. We focused on the Dunedin Pace of Aging Computed from the Epigenome (DunedinPACE). We fitted multivariable models with interaction terms. Results: Prevalence of depression was statistically higher in women (p < 0.001). MedDiet adherence was strongly and inversely associated with depressive symptoms in the whole population (p < 0.01), while the MEQ score was inversely associated (p < 0.05). In the joint analysis, both MedDiet adherence and chronotype remained statistically associated with the BDI-II score (p < 0.05), showing additive effects. No interaction effects were observed. In women, a higher score in depressive symptoms was significantly associated with faster age acceleration (measured with the DunedinPACE biomarker). This association remained significant even after adjustment for MedDiet adherence and chronotype. Conclusions: In older subjects with metabolic syndrome, the eveningness chronotype was associated with greater depressive symptoms, but a higher adherence to the MedDiet could potentially counteract the chronotype risk with additive effects. Women showed stronger associations, and importantly, we reported for the first time in this population that depressive symptoms were associated with accelerated aging.